An Innovative Method of Delivering Nebulized Medications for Perioperative Bronchospasm. Issue 1 (January 2021) - Dekel, Alex M.; Price, Ryan; Tsai, Alexander C.; Kim, Eugene
Abstract : Perioperative bronchospasm is a common challenge to anesthetic care. The timely delivery of inhaled medications can be challenging, particularly in pediatric patients and in locations where dedicated resources and respiratory support teams are limited. The delivery of nebulized medication to an intubated patient in the operating room can be difficult. We present an innovative method for delivery of nebulized solutions, in which a jet nebulizer is paired with a Mapleson hyperinflation system. Abstract : Supplemental Digital Content is available in the text.